The Phenomenon of Targumism in the Aramaic Version of the First and Second Books of Chronicles - Kuśmirek, Anna (Collectanea Theologica, 2021)
The main objective of the article is to show the features of the Aramaic translation of the First and the Second Books of Chronicles, which belongs to late Targums. The work presents the main data related to the authority, date and origin of the Targum and its manuscripts, as well as a review of major translation techniques and the method of rabbinic interpretation, which are all important elements of targumism. Linguistic changes, as well as cultural and religious ones, conditioned by various processes that occurred in the community of believers in YHWH over the centuries, were reflected in a variety of interpretative tendencies.